Simulation study of carrier to inference power ratio enhancement in orthogonal frequency division multiplexing system - S. Y., Sharifah; Fisal, Norshila; Muladi, M. (Akademik Sains Malaysia, 2007)

(untitled)
Orthogonal Frequency Division Multiplexing (OFDM) is a successful technique in wireless communication systems. Frequency offset in the OFDM system leads to loss of orthogonality among subcarriers which results in the occurrence of intercarrier interference (ICI). To improve the efficiency of bandwidth performance in the ICI self-cancellation scheme, frequency domain partial response signaling (PRS) was investigated. In this study, the integer polynomial partial response coefficients were exploited to enhance carrier-to-interference power ratio (CIR) in the OFDM system. CIR was enhanced up to 4.1 dB to 5 dB when the lengths of PRS polynomial, K was 2 and 5, respectively.